Simulator Berbasis PLC untuk Pengaturan Lalu-lintas Jalan Raya pada Perlintasan Jalur Kapal - Arief Goeritno; Sandi Tirta (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2020)
A PLC based simulator has been assembled for controlling road traffic at ship line crossings. The objectives of this study include (i) assembling a miniature bridge body, a lift-drop back mechanism for highway traffic at ship crossings, and an operating system based on a programmable logic controller (PLC) and (ii) measuring the performance of the operating system through its presence input-output signal. Assembly with the following stages: (i) implementation of miniature bridge construction; (ii) selection and placement of sensors; (iii) installation of pumps for hydraulic systems; (iv) installation of servo motor assisted latches; (v) installation of traffic control lights and indicators; and (vi) manufacture of operation panels, wiring, and installation of PLC systems. Mitsubishi PLC system programming is based on compiling algorithms and ladder diagrams with GX Works-2 32 bit. Performance measurement includes (i) when synchronization between the operating system and control on the PLC in the form of input from the operation panel and sensors on the input line are processed in the PLC program to produce an output in the form of appropriate and precise control, (ii) when the sensors installed in the system operation has functioned as programmed into the PLC, and (iii) during the process of lifting and lowering the miniature of the bridge body, there is a time difference of 26 seconds with the condition that the lifting time is longer than the time of lowering the miniature bridge body. The general conclusion is that the miniature of the bridge body and the operating system that has been built can be used as a simulator for the existence of a bridge that can be lifted and lowered again as a highway traffic lane at a ship crossing.